Transformation of Citizenship Towards Digital Citizenship in the Prospect of Global Citizenship Law - Indriyana Dwi Mustikarini; Gisheila Paulonia Ambarwati; Verina Febrianti Puspitasari (Activa Yuris: Jurnal Hukum, 2026)
Traditional citizenship law has historically been firmly rooted in the concept of territorial sovereignty, which treats a state's physical boundaries as the primary determinant of an individual's legal status. However, the rapid pace of digital globalization and the emergence of the digital nomad phenomenon have begun to erode these national boundaries. This research aims to analyze the paradigm shift from physical citizenship to digital citizenship and identify future challenges facing global citizenship law. Using normative legal research methods through conceptual and comparative approaches, this article examines the state's relationship with transnational mobility within cyberspace. The results show that this conventional concept of citizenship is undergoing a transformation toward more flexible forms, such as the emergence of digital residency initiatives and digital passports. This transformation opens up opportunities for creating a more inclusive and efficient global population administration system. Furthermore, this paradigm shift also raises complex new legal challenges, particularly regarding international tax recognition, human rights protection for cross-border workers, the potential loss of state sovereignty, and violations of private international law. This article concludes that future global citizenship law requires the restructuring and harmonization of multilateral regulations to accommodate digital citizens without compromising the security and sovereignty of nation-states.